(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
The article examines the current issues of improving state control and supervision in the field of entrepreneurial activity in the context of administrative reforms being carried out in the Republic of Uzbekistan. Special attention is paid to the legal nature of deregulation as a mechanism for reducing administrative burden and improving management efficiency. Using the example of the Republic of Karakalpakstan, legislative and organizational measures to support businesses, including tax and financial benefits, subsidies, creating a favorable investment climate, and developing infrastructure, are analyzed. It is concluded that for sustainable socio-economic growth, it is necessary to find a balance between effective control and entrepreneurial freedom.